Radiation damage studies of Fe-Cr alloys for Fusion applications using ion beams - Kotsina, Z.; Apostolopoulos, G.; Mergia, K.; Messoloras, S.; Lagoyannis, A.; Harissopulos, S. (HNPS Advances in Nuclear Physics, 2012)
Ferritic-martensitic steels are considered as prime candidates for the first wall and blanket structural materials in future Fusion Power Plants. They are based on Fe-Cr alloys with Cr concentration up to 15%. Therefore, as a first step towards understanding the irradiation behaviour of these steels, the study of pure Fe-Cr alloys as a model system plays an important role. The flexibility offered by ion beams in accurately defining irradiation conditions, allows us to perform controlled experiments that will aid in the validation of recent theories of radiation damage. Radiation damage studies of Fe-Cr alloys were performed at the TANDEM accelerator of NCSR "Demokritos" by using a 5MeV proton beam directly on the sample and reaching fluences of ~1016 protons/cm2. A specialized irradiation facility has been developed at the TANDEM accelerator with good control of irradiation temperature and with the additional capability of measuring the electrical resistivity of the sample in-situ during irradiation, to directly asses the radiation damage evolution. Proton irradiations were carried out from cryogenic temperatures of 40K up to 400K. In alloys under irradiation, apart from the lattice damage created by the irradiating particles, the large amount of energy imparted locally to atomic sites may lead to a redistribution of solutes. It is expected that at cryogenic temperature solute redistribution will be greatly suppressed, since atomic movement is completely "frozen". Comparing the results of low and high temperature irradiations enables us to distinguish between the two sources of radiation induced changes to the alloy.